Penguatan Usaha Mandiri Diversifikasi Produk Jahe melalui Penyuluhan Pemilihan Kemasan Pemasaran Digital dan Perizinan Produk - Setiawan, Vendra; Krisnawan, Alfian Hendra; Indarini, Indarini (LP2M INSURI Ponorogo, 2023)
To survive the Covid-19 epidemic, businesses must employ innovative and important methods, one of which is functional food diversification for product expansion and higher selling value. However, some beginner entrepreneurs still do not understand this strategy, which causes the business to not develop, including what is experienced by partners. The goal of this community service project is to expand partners' knowledge of the marketing of diverse functional food products made from ginger, which was previously done in product production training. Marketing knowledge was provided through counseling methods related to digital marketing, packaging selection, and product licensing. The partners of this activity are the PKK group of RW 06 Rungkut Lor, Rungkut District, Surabaya. Participatory Action Research (PAR) with a counseling mechanism is the community service strategy adopted. Evaluation of increased knowledge using the pretest and posttest methods. The questions' components include the marketing process, marketing mix, digital marketing, general understanding of product licensing, and information related to NIB, PIRT permits, halal certificates, and BPOM food permits. According to the evaluation findings, there was a 9.59% gain in expertise in digital marketing outreach efforts and a 33.33% rise in product licensing outreach activities. It is envisaged that this increase in learning would aid in the resolution of partner product marketing issues and boost partner economic welfare.